2021
DOI: 10.1002/ppul.25621
|View full text |Cite
|
Sign up to set email alerts
|

Clinical course and cost assessment of infants with a first episode of acute bronchiolitis presenting to the emergency department: Data from the GUERANDE clinical trial

Abstract: Introduction: Bronchiolitis is the leading cause of hospitalization for infants but its economic burden is not well documented. Our objective was to describe the clinical evolution and to assess the 1-month cost of a first episode of acute bronchiolitis presenting to the emergency department (ED).Methods: Our study was an epidemiologic analysis and a cost study of the cohort drawn from the clinical trial GUERANDE, conducted in 24 French pediatric EDs. Infants of 6 weeks to 12 months of age presenting at pediat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…Many studies have shown that the disease burden extends beyond affected children, impacting caregivers, leading to a loss of work productivity and increased hospitalization costs ( 17 ). Butel et al estimated an average total cost per patient of around EUR 2000 (equivalent to USD 2163) for the first episode of acute bronchiolitis, mainly attributed to hospitalization costs ( 18 ). Prior to COVID-19, RSV accounted for 5.4% of all detected positive respiratory pathogens in the United States between December 2019 and March 2020.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have shown that the disease burden extends beyond affected children, impacting caregivers, leading to a loss of work productivity and increased hospitalization costs ( 17 ). Butel et al estimated an average total cost per patient of around EUR 2000 (equivalent to USD 2163) for the first episode of acute bronchiolitis, mainly attributed to hospitalization costs ( 18 ). Prior to COVID-19, RSV accounted for 5.4% of all detected positive respiratory pathogens in the United States between December 2019 and March 2020.…”
Section: Discussionmentioning
confidence: 99%
“…The majority of the costs were due to hospitalization costs (€1418; 74%) and the rest were due to families' costs (€421; 22%) and due to employers (€80; 4%). 17 One German study including 77 hospitalized infants with bronchiolitis reported €81 costs for parents in 2005. 12 The study defined parental costs as a direct nonmedical cost that included supplemental childcare, transportation, absence from work, and additional expenses.…”
Section: Discussionmentioning
confidence: 99%
“…In a French study including 777 hospitalized infants with bronchiolitis, the average total cost for the society was €1919 per patient. The majority of the costs were due to hospitalization costs (€1418; 74%) and the rest were due to families' costs (€421; 22%) and due to employers (€80; 4%) 17 . One German study including 77 hospitalized infants with bronchiolitis reported €81 costs for parents in 2005 12 .…”
Section: Discussionmentioning
confidence: 99%
“…Severe RSV disease is associated with caregiver loss of work productivity, increased hospitalization costs due to intensive care unit admission and ventilatory support, and long-term complications, including abnormal lung function, with bronchial hyper-responsiveness and recurrent wheezing [ 10 ]. Many studies have identified a substantial economic burden on healthcare systems, governments, and society [ 11 , 12 , 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…In France, Butel and colleagues calculated an average total cost per patient of around EUR 2000 of a first episode of acute bronchiolitis, mostly due to hospitalization costs [ 11 ].…”
Section: Introductionmentioning
confidence: 99%